2013
DOI: 10.1016/j.bspc.2013.05.006
|View full text |Cite
|
Sign up to set email alerts
|

A new algorithm for wavelet-based heart rate variability analysis

Abstract: One of the most promising non-invasive markers of the activity of the autonomic nervous system is Heart Rate Variability (HRV). HRV analysis toolkits often provide spectral analysis techniques using the Fourier transform, which assumes that the heart rate series is stationary. To overcome this issue, the Short Time Fourier Transform is often used (STFT). However, the wavelet transform is thought to be a more suitable tool for analyzing non-stationary signals than the STFT. Given the lack of support for wavelet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The LF (0.04-0.15 Hz) and HF (0.15-0.4 Hz) components were extracted using an east asymmetric Daubechies wavelets with a length of 8 samples. Maximum error allowed was set as 0.01 (García, Otero, Vila, & Márquez, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The LF (0.04-0.15 Hz) and HF (0.15-0.4 Hz) components were extracted using an east asymmetric Daubechies wavelets with a length of 8 samples. Maximum error allowed was set as 0.01 (García, Otero, Vila, & Márquez, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, because of the half-wave symmetry found in electrical signals (i.e., for a periodic signal g(t) of period P, a half-wave symmetry is characterized by g(t + P/2) = −g(t)), the sinusoid frequencies f i are odd-order harmonics of the fundamental frequency. Note that the nominal value (50 Hz) of the network fundamental frequency is a priori known, but due to its fluctuations around this value over time (i.e., f 0 = 50 + δf ), we have observed that for a correct modeling, f 0 should be considered as unknown and hence one needs to re-estimate the fundamental frequency value for each transient signal 1 .…”
Section: Data Modelingmentioning
confidence: 99%
“…Studying transient phenomena is important and useful in many fields such as biomedical research for the analysis of heart rate variability [1], the extraction of detailed information of muscle behavior [2], and the detection and classification of epileptic spikes [3]; mechanics for the study of the susceptibility of structures to vibration issues [4]; and for seismic events detection and temporal localization [5,6]. Monitoring electrical loads and systems is particularly one of the areas where transients play a central role.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, wavelet transform (WT) based compression methods have become popular [13][14][15][16][17][18]. The multiresolution property of the WT grossly segments the morphological features (P-wave, QRS-complex and T-wave) of the ECG signal into different subbands [15,16,19].…”
Section: Introductionmentioning
confidence: 99%